Changes in Chinese students' academic emotions after examinations: Pride in success, shame in failure, and self‐loathing in comparison. (14th October 2022) - Fang, Jinjing; Brown, Gavin T. L.; Hamilton, Richard
Abstract: Background: Several attempts have been made to examine students' academic emotions (AEs) in Western contexts, but less is known about how students' self‐reported emotions vary over time. Aims: The study aimed to understand Chinese students' emotional responses to academic events and the impact of high‐stakes testing on their AEs in the first year with a repeated‐measures survey after the Semester 1 and Semester 2 mid‐term examinations. Samples: 351 first‐year university students completed both surveys in an elite Chinese university, where the top 10% of first‐year students were assigned to an honours programme. Methods: Self‐reported AEs survey responses were evaluated with confirmatory factor analysis. Invariance testing between honours and ordinary students and between semesters was used to examine between‐group differences across time. Results: A three‐factor model of AEs (i.e., admired, shame, and self‐loathing) was found in both semesters, with strong invariance between semesters. Mean scores between groups were equivalent and semester. However, self‐loathing had the lowest mean (mean = 2.50; between mostly disagree and slightly agree), admired was at moderately agree (mean = 4.00), and shame was strongest at just over moderately agree (mean = 4.20). Conclusions: This study reveals a three‐factor structure of AEs and the stability of these emotions among highly successful Chinese learners. Despite being elite students, this sample of Chinese learners felt shame and pride in response to mid‐term examinations.